Strategi Pengembangan Usaha Halal Pengolahan Bandeng oleh Kelompok Paguyuban Masyarakat Desa Junok Sreseh Sampang - Ulfiyah Ulfiyah; Mashudi Mashudi; Dahruji Dahruji (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Junok Village, Sreseh District, Sampang Regency has a favorite milkfish that is liked by consumers in the surrounding sub-districts and other consumers. Based on the availability of abundant milkfish resources, the milkfish processing business in Junok village has not been fully developed. So research activities are carried out. This study aims to find out how the Halal Business Development Strategy of Milkfish Processing by the Junok Sreseh Sampang Village Community Association. This study uses a qualitative descriptive research method and uses a field study approach. Data collection techniques were obtained by interview and observation methods. By using data collection, data reduction, data presentation, and conclusions in analyzing data. The results of the study show that the Halal business development strategy in Junok Village has not been fully implemented, as seen from several important aspects that still need attention. Although there is awareness of the importance of halal products, many producers in Junok Village do not have official halal certification, which can increase consumer confidence, so training is needed to increase understanding of halal, as well as collaboration with related institutions to help producers obtain halal certification.